Cuidadores de pacientes demenciales y su estado de salud mental - Andrade Colito, Cleidivanie (Machala : Universidad Técnica de Machala, 2019)
Throughout time, the relationship between youth and demographic rates ensured that the distribution of the population remained unchanged, that is, there was a predominance of youth over old age. Due to the gradual fall of patients with dementia, it is required that the functionalities of the individual's daily life become accepted by the caregiver and can bring negative consequences in the caregiver physically, emotionally, socially and financially. Course objective: To describe mental disorders in caregivers of insane patients. Specific objectives: identify the most frequent mental disorders in people who care for insane patients and assess the quality of life of the caregiver of insane patients. METHOD: In the present work a bibliographic review was carried out recompiling information from the year 2013 to the current year in electronic scientific journals such as: Google Academic, Pubmed, Science Direct. Neurosciece, PMC, Scielo, Dialnet also obtained information from guides of the Ministry of Public Health. CONCLUSIONS: The depressive state has a higher incidence in informal caregivers. The high level of stress damages the work of the formal caregiver due to lack of motivation.
A lo largo del tiempo, la relación entre la juventud y las tasas de demografía aseguraban que la distribución de la población permaneciera invariable, o sea, había un predominio de la juventud sobre la edad avanzada. Por la caída gradual de los pacientes con demencia, es requisito que las funcionalidades de la vida diaria del individuo pasen a ser asumidas por el cuidador y puede traer secuelas negativas en el cuidador a nivel físico, emocional, social y financieramente. Objetivo general: Describir los trastornos mentales en los cuidadores de pacientes demenciales. Objetivos específicos: identificar los trastornos mentales más frecuentes en personas cuidadoras de pacientes demenciales y valorar la calidad de vida del cuidador de pacientes demenciales. MÉTODO: En el presente trabajo se realizó una revisión bibliográfica recopilando información desde el año 2013 al año vigente en revistas científicas electrónicas tales como: Google Académico, Pubmed, Science Direct. Neurosciece, PMC, Scielo, Dialnet además también se obtuvo información de guías del ministerio de salud pública. CONCLUSIONES: El estado Depresivo tiene mayor incidencia en los cuidadores informales. El alto nivel de estrés perjudica el trabajo del cuidador formal debido a falta de motivación.
Keywords: CUIDADORES; DEMENCIA; CALIDAD DE VIDA; TRASTORNOS MENTALES